3D Bioprinting in Skeletal Muscle Tissue Engineering. Issue 24 (23rd April 2019) - Ostrovidov, Serge; Salehi, Sahar; Costantini, Marco; Suthiwanich, Kasinan; Ebrahimi, Majid; Sadeghian, Ramin Banan; Fujie, Toshinori; Shi, Xuetao; Cannata, Stefano; Gargioli, Cesare; Tamayol, Ali; Dokmeci, Mehmet Remzi; et al.
Abstract: Skeletal muscle tissue engineering (SMTE) aims at repairing defective skeletal muscles. Until now, numerous developments are made in SMTE; however, it is still challenging to recapitulate the complexity of muscles with current methods of fabrication. Here, after a brief description of the anatomy of skeletal muscle and a short state‐of‐the‐art on developments made in SMTE with "conventional methods, " the use of 3D bioprinting as a new tool for SMTE is in focus. The current bioprinting methods are discussed, and an overview of the bioink formulations and properties used in 3D bioprinting is provided. Finally, different advances made in SMTE by 3D bioprinting are highlighted, and future needs and a short perspective are provided. Abstract : 3D bioprinting in skeletal muscle tissue engineering (SMTE) is discussed in this Review. After a short state‐of‐the‐art on SMTE with "conventional methods, " 3D bioprinting methods are in focus, and an overview of the bioink formulations and properties are provided. Different advances made in SMTE with 3D bioprinting are highlighted, and future needs and a short perspective are provided.